2015
DOI: 10.1039/c4ta04993d
|View full text |Cite
|
Sign up to set email alerts
|

Vertically aligned nanocomposite La0.8Sr0.2CoO3/(La0.5Sr0.5)2CoO4 cathodes – electronic structure, surface chemistry and oxygen reduction kinetics

Abstract: The hetero-interfaces between the perovskite (La 1Àx Sr x )CoO 3 (LSC 113 ) and the Ruddlesden-Popper (La 1Àx Sr x ) 2 CoO 4 (LSC 214 ) phases have recently been reported to exhibit fast oxygen exchange kinetics.Vertically aligned nanocomposite (VAN) structures offer the potential for embedding a high density of such special interfaces in the cathode of a solid oxide fuel cell in a controllable and optimized manner.In this work, VAN thin films with hetero-epitaxial interfaces between LSC 113 and LSC 214 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 56 publications
3
92
0
Order By: Relevance
“…As shown in Figure 5, Ma et al 48 showed, in the temperature range of 320-400 • C, CoO 4 films. Therefore, the higher reactivity of the VAN surface to the oxygen reduction reaction is attributed to enhanced electron availability for charge transfer as well as the suppression of detrimental cation segregation.…”
Section: B Solid Oxide Fuel Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 5, Ma et al 48 showed, in the temperature range of 320-400 • C, CoO 4 films. Therefore, the higher reactivity of the VAN surface to the oxygen reduction reaction is attributed to enhanced electron availability for charge transfer as well as the suppression of detrimental cation segregation.…”
Section: B Solid Oxide Fuel Cellsmentioning
confidence: 99%
“…Very recently, as shown in Figure 1(d), new and novel device architectures, vertically aligned nanostructured (VAN) films, [43][44][45][46][47][48][49][50][51][52][53] were developed to overcome several issues in conventional ionic devices as mentioned above. Basically, the development of ionic devices by using VAN films started from a similar motivation of laterally aligned heteroepitaxy films.…”
Section: New Device Architectures For Ionic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pore-free film samples with a high TPB density were prepared either by surface decoration of a dense P film with small amounts of R 5-7 (see Fig. 1b), or by phase separation during PLD 8,12 (Fig. 1c).…”
Section: -11mentioning
confidence: 99%
“…(La,Sr)CoO 3-δ /(La,Sr) 2 CoO 4±δ (perovskite phase, P/RuddlesdenPopper phase, R) two-phase materials were reported in literature to show enhanced activity for the oxygen reduction reaction (ORR) compared to reference single-phase samples [1][2][3][4][5][6][7][8][9][10][11] making them a promising new material for highly active cathodes in intermediate temperature solid oxide fuel cells. This enhancement was attributed to effects at the P/R/O 2 triple phase boundary (TPB).…”
mentioning
confidence: 99%